2017
DOI: 10.1111/chd.12555
|View full text |Cite
|
Sign up to set email alerts
|

Body composition, appetite-related hormones, adipocytokines, and heart failure in adult patients with congenital heart disease: A preliminary study

Abstract: Objectives: To assess body composition and relationships among body composition, appetiterelated hormones, adipocytokines, and heart failure (HF) in adult patients with congenital heart disease (CHD).Patients: This prospective study enrolled 46 consecutive adult patients with CHD and 12 agematched healthy controls. The patients and control subjects were divided into four groups: 13 patients with Fontan circulation (group A), 16 patients with cyanosis (group B), 17 patients who previously underwent biventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The decreased ghrelin levels following the diagnosis of DCM are consistent with previous studies on HF of different etiology [23]. Ghrelin has a favorable effect on cardiovascular function and has been considered as a potentially therapeutic hormone [39]. Further studies should address factors associated with the response to ghrelin such as to directly assess how the etiology of heart failure impacts on the downregulation of GHSR and to identify if inflammation or other factors may modulate GHSR expression and ghrelin sensitivity, in a way to reverse ghrelin resistance and to restore its protective effects on the myocardium.…”
Section: Discussionsupporting
confidence: 85%
“…The decreased ghrelin levels following the diagnosis of DCM are consistent with previous studies on HF of different etiology [23]. Ghrelin has a favorable effect on cardiovascular function and has been considered as a potentially therapeutic hormone [39]. Further studies should address factors associated with the response to ghrelin such as to directly assess how the etiology of heart failure impacts on the downregulation of GHSR and to identify if inflammation or other factors may modulate GHSR expression and ghrelin sensitivity, in a way to reverse ghrelin resistance and to restore its protective effects on the myocardium.…”
Section: Discussionsupporting
confidence: 85%
“…20 Shiina et al also found that Fontan patients have reduced muscle mass when compared to controls, but their analyses were not sex-stratified. 21 This renders it difficult to interpret their results and correlate them with our findings, since it is known that the muscular composition of men and women is very different.…”
mentioning
confidence: 71%
“…Fontan associated myopenia, defined as a lean muscle mass Z-score of −2 or lower, is present in 39% of Fontan patients ( 63 ). Bio-impedance measurements and MRI-derived muscle mass estimations—which are more easily obtained estimations of muscle mass- are also abnormal for Fontan patients ( 64 66 ). No studies directly compared these methods of lean muscle mass estimation to current gold standards.…”
Section: Resultsmentioning
confidence: 99%
“…Shiina et al in a prospective study of 46 adult Fontan patients, showed that in the Fontan patient group plasma ghrelin levels, a hormone primarily related to increased appetite, were lower than those in controls ( P < 0.05) ( 66 ). Ghrelin is an orexigenic hormone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation